Estimates of Unionism and Collective Bargaining in Canada - Kumar, Pradeep (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
This paper presents new estimates of unionization and collective bargaining coverage for Canada from a special Statistics Canada household survey conducted in December 1984. The new estimates are comparee with the old estimates.